The absolute and the restricted, and their meanings - Auzar, Nurul Iffah Nadzirah; Nor Azmi, Nurul Nabila; Saipul Bahrin, Ra’isah Syadiah; Mohd Zanawawi, Norsyamin Nadira; Abdul Samad, Aida Syazwana (2025)
Slide presentation for "The absolute and the restricted, and their meanings"